Selective Deposition of Compositionally Graded Hybrid Adhesive Films. Issue 17 (9th September 2015) - Giachino, Marta; Watson, Brian L.; Dubois, Geraud; Dauskardt, Reinhold H.
Abstract : Hybrid organic–inorganic materials that are compositionally graded are excellent candidates for addressing the challenges related to the bonding of polymeric layers and inorganic substrates. Often, the synthesis of these hybrid materials involves the use of kinetically driven and dynamic solution systems where obtaining the desired hybrid molecular structures in the deposited film is not trivial. A coating process is used to selectively deposit a small fraction of the total species in solution with an optimized molecular weight, resulting in compositionally graded hybrid films that are organic‐rich toward the top and inorganic‐rich toward the bottom. This selective deposition technique provides a unique knob to fine tune the molecular structure of films deposited from dynamic solution systems, resulting in hybrid organic–inorganic films that exhibit an eightfold increase in adhesion of an epoxy/silicon interface. Abstract : An adhesive hybrid organic−inorganic film that is compositionally graded is synthesized using sol‐gel chemistry. The graded structure forms by selectively depositing species in solution with an optimized molecular weight, resulting in the enrichment of organic species on the top surface of the film. As a result, the film improves the adhesion of polymer/silicon interfaces by up to eightfold.